A note on certain maximal curves. Issue 2 (1st February 2017) - Tafazolian, Saeed; Torres, Fernando
ABSTRACT: We characterize certain maximal curves over finite fields whose plane models are of Hurwitz type, namely x m y a + y n + x b = 0 . We also consider maximal hyperelliptic curves of maximal genus. Finally, we discuss maximal curves of type y q + y = x m through class field theory.